Outcomes of a Multicenter, Prospective, Crossover, Randomized Controlled Trial Evaluating Subperception Spinal Cord Stimulation at ≤1.2 kHz in Previously Implanted Subjects. Issue 1 (2nd July 2019) - North, James; Loudermilk, Eric; Lee, Albert; Sachdeva, Harsh; Kaiafas, Demetrios; Washabaugh, Edward; Sheth, Samir; Scowcroft, James; Mekhail, Nagy; Lampert, Benjamin; Yearwood, Thomas; Shaw, Erik; et al.
Abstract : Objective: The WHISPER randomized controlled trial (RCT) evaluates safety and clinical effectiveness of subperception spinal cord stimulation (SCS) at ≤1.2 kHz in subjects previously implanted with an SCS system for treatment of chronic, neuropathic pain. Methods: WHISPER is a prospective, multicenter RCT with a crossover design sponsored by Boston Scientific, Marlborough, MA (ClinicalTrials.gov : NCT02314000). Eligible subjects were randomized ( N = 140) to receive subperception or supraperception for three months and then crossed over to receive the alternative. Upon completion of crossover period, subjects who preferred subperception were followed up to one year. Overall pain, quality‐of‐life, and other outcomes were collected in the study. The primary endpoint was the overall pain responder rate (≥50% improvement from baseline) with no increase in medications. Secondary endpoints consisted of pain scores, physical disability, quality of life, and treatment preference. Results: The study met its primary endpoint and demonstrated noninferiority between supraperception and subperception in a prespecified cohort of 70 randomized subjects (Interim Analysis). Thirty‐nine percent of subjects with subperception settings and 29% with supraperception settings had a greater than or equal to 50% reduction in their overall pain scores with no increase in average daily medication at three‐months post‐activation as compared with baseline. Further assessment of all participating study subjects ( N = 140) revealed similar results. Subjects were previously implanted 3.8 ± 2 years and had a disability score (Oswestry Disability Index) of 70.2 ± 11.4 at study start. Of the randomized subjects that completed the End of Period 2 Visit, 93 (66%) preferred subperception SCS and their mean overall pain reduced from 7.3 ± 1.1 ( N = 89) at baseline to 4.0 ± 2.1 ( N = 80) at 12‐months post‐activation. Post hoc analysis also demonstrated that multiple options provide superior outcomes, as supported by a 74% increase in the responder rate when subjects could choose their most effective option (47%) compared with supraperception alone (27%). Discussion: Subperception SCS at ≤1.2 kHz is safe and effective in subjects with extreme physical disability and previously implanted for chronic pain. Further, by providing study participants with different waveform options, increased pain relief was achieved.